Effects of Ion Exchange Process on Catalyst Activity and Plasma-Assisted Reactor Toward Cracking of Palm Oil into Biofuels - Istadi Istadi; Luqman Buchori; Didi Dwi Anggoro; Teguh Riyanto; Anindita Indriana; Chusnul Khotimah; Fachmy Adji Pangestu Setiawan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Biofuels can be produced through a conventional catalytic cracking system and/or a hybrid catalytic-plasma cracking system. This paper was focused on studying effect of Na+ ion exchange to HY-Zeolite catalyst on catalyst performance to convert palm oil into biofuels over a conventional continuous fixed bed catalytic cracking reactor and comparing the catalytic cracking performance when carried out in a continuous hybrid catalytic-plasma reactor. The catalysts were characterized by X-ray Diffraction (XRD) and Bruneuer-Emmet-Teller (BET) surface area methods. The biofuels product were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) to determine the hydrocarbons composition of biofuels product. From the results, ion exchange process of Na+ into HY-Zeolite catalyst decreases the catalyst activity due to decreasing the number of active sites caused by blocking of Na+ ion. The selectivity to gasoline ranges achieved 34.25% with 99.11% total conversion when using HY catalyst over conventional continuous fixed bed reactor system. Unfortunately, the selectivity to gasoline ranges decreased to 13.96% and the total conversion decrease slightly to 98.06% when using NaY-Zeolite catalyst. As comparison when the cracking reaction was carried out in a hybrid catalytic-plasma reactor using a spent residual catalytic cracking (RCC) catalyst, the high energetics electron from plasma can improve the reactor performance, where the conversion and yield were increased and the selectivity to lower ranges of hydrocarbons was increased. However, the last results were potential to be intensively studied with respect to relation between reactor temperature and plasma-assisted catalytic reactor parameters. Copyright © 2019 BCREC Group. All rights reserved